2016
DOI: 10.7763/ijiet.2016.v6.686
|View full text |Cite
|
Sign up to set email alerts
|

Videotaped OSPE: Is This a Right Procedure to Assess Health Science Students’ Performance? — A Pilot Study

Abstract: Abstract-The performance based student assessment during OSPE, challenge the examiners accurately capturing students' practical skills. In order to solve this problem, this study introduces a new Innovative procedure of videotaped objective structured practical examination (VOSPE) in the area of health care education to support the existing objective structured practical exam (OSPE). The purpose of this study is to introduce the videotaped OSPE among fifth semester physiotherapy students to assess their stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In the current study, the majority in fundamental nursing agreed that OSPE exam should be included. These results are consistent with Kumar (2016) [24] who reported that the OSPE is a feasible method which can be implemented in the health sciences in marking, can be used as a digital study material with concern and also as an evidence of student performance interview process.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the majority in fundamental nursing agreed that OSPE exam should be included. These results are consistent with Kumar (2016) [24] who reported that the OSPE is a feasible method which can be implemented in the health sciences in marking, can be used as a digital study material with concern and also as an evidence of student performance interview process.…”
Section: Discussionsupporting
confidence: 90%
“…Having a recording of candidates' performances offers many possibilities. [27][28][29][30][31][32][33] If an examiner is disconnected from the platform, the recording allows for scoring of the performance later thus not penalizing the candidate. In addition, the recording can be used in the case of a candidate contesting their score.…”
Section: Record Performances As a Safety Netmentioning
confidence: 99%